Development and validation of a questionnaire on normative organizational commit-ment: A pilot study in Mexicans workers. - Betanzos-Diaz, Norma; Rodríguez-Loredo, Cynthia Shugey; Paz-Rodríguez, Francisco (Anales de Psicología / Annals of Psychology, 2017)
A questionnaire for measuring commitment in its normative dimension, based on reciprocity and responsibility as value to the work where a link to the organization based on loyalty of workers set was developed. An initial 30 item bank, built and reviewed with rigorous criteria were applied to a sample of 298 employees in a departament store chain (168 women, 56.4%, 130 men), aged between 18 and 65 (M = 32.5, SD = 9.6) years and schooling Baccalaureate (199, 67.8%). The seniority ranging from 1 to 34 years (M = 4.4 years, SD = 5.7). Using exploratory factor analysis with 28 items two factors explaining 45.1% of variance was identified: the first known loyalty-reciprocity; and the second compliance-responsibility. Reliability analysis indicated adequate internal consistency, α = .88. Concurrent validity was assessed by Pearson correlation with Organizational Commitment Questionnaire and Scale Values to Work. The results indicated that the dimensions of the Organizational Commitment Questionnaire Standards may be an option to assess this construct.